Flutamide Influences Placental Aldo–Keto Reductase Family 1 Member C1 (AKR1C1) Expression in Pigs. Issue 1 (5th December 2013) - Grzesiak, M; Knapczyk‐Stwora, K; Wieciech, I; Golas, A; Slomczynska, M
Contents: Aldo–keto reductase family 1 member C1 (AKR1C1) catalyses the conversion of progesterone into inactive 20 α ‐dihydroxyprogesterone. It is suggested that AKR1C1 expression in the placenta prevents from the cytotoxic effect of progesterone on foetuses during late pregnancy. The aim of the study was to determine whether the anti‐androgen flutamide administered during late pregnancy (83–89 days of gestation) or before parturition (101–107 days of gestation) influences AKR1C1 expression in the porcine placenta. AKR1C1 mRNA and protein levels were measured using real‐time PCR and western blotting, respectively. Immunolocalization of AKR1C1 within placentas was also performed. Flutamide significantly increased AKR1C1 mRNA (p = 0.008) and protein (p = 0.019) expression only during the pre‐parturient period in pigs. AKR1C1 protein was immunolocalized in the epithelial and stromal cells of foetal and maternal part of placenta at both stages of gestation. Following flutamide treatment, the intensity of staining was higher (p = 0.045) on day 108 of gestation. In conclusion, porcine placental AKR1C1 expression seems to be regulated by an androgen signalling pathway and may be involved in foetal survival by preventing the detrimental effect of progesterone.